Nilai Islam dalam Tradisi Haul Masyarakat Muslim Desa Gubugsari - Icha Arzeti Pratiwi; Nabila Meidiana; Muhammad Rifqi Hawari; Fitri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Haul tradition is one of the religious rituals that is still preserved by the Muslim community in Gubugsari village. Haul is a commemoration of the death of someone who is considered to have privileges, such as ulama, kiai, or respected community leaders. This ritual is generally carried out every year on the day of the death of the person being commemorated. In the context of Gubugsari village, the haul tradition has become an inseparable part of the life of the local Muslim community. This ritual is not only a form of respect for the commemorated person, but also a forum for the community to strengthen ties, strengthen religious identity, and preserve Islamic values that have taken root in local culture. As the haul tradition in the village of Gubugsari, Pegandon Subdistrict, Kendal Regency, which until now still carries out the haul tradition because the person who is honored is mbah Abdul Wahab as a respected figure by the Muslim community, especially in the village. To see the values of these traditions, researchers are interested in further examining the values of the haul tradition of cengklian and ndangdoan in the socio-religious life of the Candimulyo village community, Sedan sub-district, Rembang district. The method used in this research is qualitative method, data collection techniques in this research using observation, documentation and interviews. The subjects in this study were the people of Gubusari village, both those who joined the committee and those involved in the haul tradition event The results of this study indicate that the haul tradition has a form of a series of haul event contents, namely the practices performed during the pilgrimage as a medium for the tradition. The benefits of religious values are increasing our devotion to Allah SWT